PEMODELAN STRUKTUR RANGKA DINDING PENGISI BERATURAN UNTUK GEDUNG 4, 7 DAN 10 LANTAI DENGAN VARIASI PENEMPATAN DINDING PENGISI PADA LANTAI DASAR - Tirta Sari, P. A. Parmaheni; Sukrawa, M.; Budiwati, I. A. M. (JURNAL SPEKTRAN, 2014)
Research on reinforced concrete structure with and without infill wall has been done by modeling the same structure as open frame (OF) and infilled frame (RDP) to compare in their stiffness, force distribution and dimensional changes. In RDP model, the wall is modeled as equivalent diagonal struts with one, two and three struts. Seven-storey building structure is taken as a reference and structures of 4 and 10 floors are used as comparison. To observe the effect of wall discontinuity at ground level additional 4 models were made for the 7 storey building by removing one, four, six, and all nine walls at ground level (RDP7S3SS1, RDP7S3SS2, RDP7S3SS3, and RDP7S3SS4). For seven-storey model, RDP structures with one, two, and three struts have a comparable lateral stiffness but it tends to increase for model with many struts. Compared to OF, RDP structure with one, two, and three struts have smaller lateral deformation with ratio 0,655; 0,636, and 0,612, respectively. Bending moment, shear and axial in the frame of RDP are also smaller than those of OF with ratio 0,223 and 0,916. RDP model with 3 struts gives better force distribution on the frame compared to the model with single strut. Removing all walls at ground level produce inter storey drift ratio of 4, which is a soft storey phenomenon. On the 4, 7, and 10 storey variation the lateral deformation ratio for RDP and OF are 0,547; 0,612, and 0,581, respectively. The cross sectional area of frame for RDP is as low as 40% compared to that of OF.
Keywords: Infilled frame, equivalent diagonal strut, soft storey collapse